2017
DOI: 10.3390/molecules22091529
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resveratrol on Inflammation and Oxidative Stress in a Rat Model of Chronic Obstructive Pulmonary Disease

Abstract: Oxidative stress and inflammation are hypothesized to contribute to the pathogenesis of chronic obstructive pulmonary disease (COPD). Resveratrol (trans-3,5,4′-trihydroxystilbene) is known for its antioxidant and anti-inflammatory properties. The study aimed to investigate the effects of resveratrol in a rat model with COPD on the regulation of oxidative stress and inflammation via the activation of Sirtuin1 (SIRTl) and proliferator-activated receptor-γ coactivator-1α (PGC-1α). Thirty Wistar rats were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 32 publications
4
85
2
1
Order By: Relevance
“…Along with this, resveratrol treatment also attenuated the cigarette smokeinduced fibrotic response and mucus hypersecretion in the lungs (Andrews et al, 2016). A recent study in rats also confirmed the efficacy of resveratrol in COPD, and that the beneficial effect of resveratrol may be exerted via the SIRT1 and PGC-1α axis (Wang, Li, Li, Miao, & Xiao, 2017). Resveratrol therapy is currently in phase 3 clinical trials for use in COPD patients (CARMENS-trial; ClinicalTrials.gov Identifier NCT02245932).…”
Section: Targeting Oxidative Stressmentioning
confidence: 80%
“…Along with this, resveratrol treatment also attenuated the cigarette smokeinduced fibrotic response and mucus hypersecretion in the lungs (Andrews et al, 2016). A recent study in rats also confirmed the efficacy of resveratrol in COPD, and that the beneficial effect of resveratrol may be exerted via the SIRT1 and PGC-1α axis (Wang, Li, Li, Miao, & Xiao, 2017). Resveratrol therapy is currently in phase 3 clinical trials for use in COPD patients (CARMENS-trial; ClinicalTrials.gov Identifier NCT02245932).…”
Section: Targeting Oxidative Stressmentioning
confidence: 80%
“…Moreover, resveratrol protects the spinal cord from ischemic damage in rats by reducing plasma levels of nitrite, AOPP and MDA, and increasing the enzymatic activity of SOD and CAT (Fu et al, 2018). Resveratrol also attenuates oxidative stress in rats with experimental periodontitis (Corrêa et al, 2018), induced early Alzheimer's disease (Lin et al, 2018) and chronic obstructive pulmonary disease (Wang et al, 2017).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Previous studies have shown that resveratrol has neuroprotective properties in NeuP, AD, and PD. It has been demonstrated that resveratrol attenuated in ammation by inhibiting the pro-in ammatory cytokine secretion in the obese model and cirrhotic model [35][36][37]. Administration of resveratrol elicits neuroprotective function via suppressing glial activation and decreasing the secretion of proin ammatory cytokines in PD mice [14,38].…”
Section: Discussionmentioning
confidence: 99%